Auto Timetable Management Mobile Application - Chai, Samuel Ye Ler; Ling, Yeong Tyng (Trends in Undergraduate Research, 2023)
In this fast-paced lifestyle, we play multiple roles and bear different responsibilities. This kind of lifestyle needs proper time management skills to look after the tasks and duties that have been entrusted. In order to do time management effectively, tools such as timetables are commonly adopted. Rescheduling of a timeslot in a timetable could happen due to certain unforeseen events that require immediate action. The rearrangement of one timeslot could possibly affect another timeslot in a timetable, essentially, it needs extra time and effort to draw new planning. In this paper, we proposed to develop an auto timetable scheduling mobile application to combat the hustle of manual timetable management. By assigning priority levels and constraints such as the preferred time and date of a task, the proposed application can reschedule and generate a new timetable automatically. With the proposed application, we claim that users can reduce the hustle of creating and managing their timetables in a manual way.